2011
DOI: 10.1111/j.1365-2230.2010.03955.x
|View full text |Cite
|
Sign up to set email alerts
|

An open-label study assessing the safety and efficacy of alitretinoin in patients with severe chronic hand eczema unresponsive to topical corticosteroids

Abstract: Oral alitretinoin 30 mg was well tolerated and effective, and provided distinct therapeutic benefits in severe CHE, as assessed by patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
28
1
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 9 publications
8
28
1
2
Order By: Relevance
“…The safety findings in TOCCATA were consistent with those in previous clinical trials (15)(16)(17)22), and confirmed the tolerability profile of alitretinoin. The most common treatment-emergent adverse reaction was headache (7.5%), followed by increased triglycé-rides and increased cholesterol.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The safety findings in TOCCATA were consistent with those in previous clinical trials (15)(16)(17)22), and confirmed the tolerability profile of alitretinoin. The most common treatment-emergent adverse reaction was headache (7.5%), followed by increased triglycé-rides and increased cholesterol.…”
Section: Discussionsupporting
confidence: 89%
“…In the clinical development programme for registration, studies of up to 6 months' duration with alitretinoin have shown that it is highly effective in the treatment of severe CHE unresponsive to potent topical corticosteroids and is well tolerated with a good safety profile (15)(16)(17). Alitretinoin was initially granted approval by several European authorities, including the German Health Authorities in autumn 2008, for the treatment of patients with severe CHE unresponsive to potent topical corticosteroids.…”
mentioning
confidence: 98%
“…However, chronic topical treatment is associated with a number of side effects [92]. Skin corticosteroid depot formation contributes to the local toxicity associated with these products, and is a consequence of the slow permeation of these drugs from the SC into the epidermis [93,94].…”
Section: Potential Applicationsmentioning
confidence: 99%
“…The DLQI consists of 10 items: (1) itching and scratching, (2) embarrassment, (3) housework, (4) dressing, (5) social relationships/spare time, (6) sport, (7) work/study, (8) partner/relatives, (9) sex, and (10) treatment. Each question relates to the last week, and ranges from 0 (no impairment) to 3 (maximum impairment).…”
Section: Datamentioning
confidence: 99%